A Study Of The Impact Of Price Uncertainty To Mining Project Valuation - M. Zhang; R. Middleton; M. Menabde (Society for Mining, Metallurgy & Exploration, 2007)
Whilst mine planners almost universally assume deterministic forward commodity prices when undertaking valuations of mining projects, historical data well demonstrates that those prices are quite volatile. This paper seeks to understand and quantify how this forward price uncertainty will impact mining project valuation. This paper will also present a way of computing an upper bound on the expected Net Present Value (NPV) of a mining project given forward commodity price uncertainty.